Accelerated curing of glued-in threaded rods by means of inductive heating – Part I: experiments. Issue 3 (17th February 2021) - Ratsch, N.; Böhm, S.; Voß, M.; Adam, M.; Wirries, J.; Vallée, T.
ABSTRACT: Adhesive bonding is nowadays an integral part of timber engineering and sets the basis for efficient joint typologies, as well as for most Engineered Wood Products (EWP). Regarding the manufacturing of joints, in particular under on-site conditions, two-component (2K) adhesives, in particular epoxies (EPX) and polyurethanes (PUR), are preferred over one component (1K) adhesives, because of their ability to cure under ambient conditions. If compared to mechanical fastening, however, the relatively slow curing of most 2K-adhesives used in practice remains a serious disadvantage. This paper summarises investigations on induction heating as a way to speed up significantly the curing process of Glued-in Rods (GiR), a joint type used in timber engineering. Firstly, four commercially available adhesives were investigated with regard to their potential for accelerated curing, resulting in the determination of maximum curing temperatures, and heating rates. Based thereupon, a series of large-scale GiR, involving threaded rods and beech Laminated Veneer Lumber (LVL), were manufactured, and inductively cured. The curing time was dramatically shortened from days to 5 min. Resulting joint capacities depended upon the time elapsed since induction. The resulting findings served as a basis for subsequent investigations to be presented in the second part of this series Figure 16 .